(untitled) (Proceedings of the Global Public Health Conference, 2019)
The Hemoglobin (Hb) concentration below 11g/dl during pregnancy leads to Iron Deficiency Anemia (IDA). As increased maternal iron needs and demands from the growing fetus and placenta, pregnant mothers are at risk of having IDA which causes many complications during pregnancy and infancy. The purpose of this study is to explore the knowledge about IDA of pregnant mothers in the first trimester. A self-administered questionnaire was distributed in this quantitative descriptive study among 180 pregnant mothers in the first trimester using convenience sampling method, at the antenatal clinics, District General Hospital, Matara. Ethical approval was obtained from the Ethics Review Committee of the National Hospital of Sri Lanka. Data was analyzed by descriptive statistics using SPSS 22 version. Significantly 80% of the respondents have identified low Hb level (<11g/dl) as IDA. Most frequently mentioned causative factors of IDA were inadequate food intake (90%), and imbalance diet (80%) while malaria (10%) and stress (1%) mentioned by only a few pregnant mothers. Sixty percent of pregnant mothers identified that milk and milk products as inhibitors in iron absorption. Two third of pregnant mothers have identified tiredness and pale color of the body as dominant signs of IDA. Most known side effects were low birth weight (32%), premature delivery (30.5%) and postpartum anemia (30%). The study showed that considerable knowledge of pregnant mothers with respect to meaning, causes, signs and, iron-rich food sources of IDA while showing comparatively poor knowledge of the effects of IDA in pregnancy. Therefore, it is recommended to have more awareness programs to further educate on the effects of IDA among pregnant mothers in the first trimester in Sri Lanka.